Imaging the serotonin transporter using (123)I-ADAM in the human brain - Chou, Yuan-Hwa; Yang, Bang-Hung; Chung, Ming-Yi; Chen, Shih-Pei; Su, Tung-Ping; Chen, Chia-Chieh; Wang, Shyh-Jen (Psychiatry research. Neuroimaging, 2009)
The aim of this study was to examine the feasibility of (123)I-ADAM to image the serotonin transporter (SERT) in Asian (Taiwanese) subjects. Single photon emission computed tomography (SPECT) scans were performed on nine healthy volunteers who were s-allele carriers at the polymorphism within the serotonin transporter promoter region (SERTPR) after intravenous bolus injection of (123)I-ADAM. Quantification of (123)I-ADAM binding was performed using the ratio equilibrium method (REM) with specific uptake ratio (SUR) and a simplified reference tissue model (SRTM). Curve-fitting techniques were used to obtain the peak equilibrium point from 241 to 301 min (average 264+/-20 min) after injection of (123)I-ADAM for the midbrain and from 215 to 270 min (average 235+/-18 min) after injection of (123)I-ADAM for the striatum. Two sets of SUR were obtained by either curve fitting (estimated values) or integrated period from 240 to 270 min (observed values). The estimated values of SUR were 2.11+/-0.51 for the midbrain and 1.50+/-0.44 for the striatum, whereas the observed values were 2.11+/-0.83 for the midbrain and 1.24+/-0.31 for the striatum. The SRTM showed that the binding potential (BP) was 2.10+/-0.66 for the midbrain and 1.35+/-0.25 for the striatum. There was a good correlation between estimated SUR, observed SUR and SRTM in the midbrain but not in the striatum. The optimal scanning duration for both the midbrain and the striatum should be 220 to 280 min similar to that suggested by previous studies in Caucasians. However, due to the low signal-to-noise ratio in the striatum, (123)I-ADAM could be an ideal tracer for imaging SERT in the midbrain but not in the striatum.